A review on thermal performance enhancement of green cooling system using different adsorbent/refrigerant pairs. (May 2022) - Chauhan, P.R.; Kaushik, S.C.; Tyagi, S.K.
Graphical abstract: Highlights: State-of-the-art on adsorbent-adsorbate pairs is presented in chronological order. Present scenario of adsorption technology based industrial chillers is discussed. Coatings of new adsorbents and improved design of adsorption reactors are addressed. The potential of biomass-based activated carbon adsorbent has been summarized. A conceptual schematic of biomass powered adsorption cooling system is proposed. Abstract: Due to the ever-increasing cooling demand, alternative refrigeration is being explored for the last few decades that are less energy-intensive and can utilize ozoenvironmental friendly working fluid. Vapor adsorption refrigeration is one of the most promising alternatives among all heat-driven refrigeration systems. One of the most important requirements in an adsorption-based cooling system is to enhance the adsorption uptake capacity of the adsorbent materials for their impactful, effective, and economical operation. However, there are several working pairs explored during the recent decades but none of them could be suitable as an ideal one, for all the operating conditions. In this article, the various characteristics of different adsorbents including the highly porous activated carbons derived from waste biomass, the composites, and compounds developed, are thoroughly reviewed. Further, the synthesization, the optimal assortment, regeneration, coatings on adsorber, and commercial application of novel adsorbents including the advanced adsorption reactors and the current scenario of industrial adsorption chillers are discussed in detail. Finally, the impact of operating parameters, such as adsorbent-adsorbate mass ratio, desorption pressure, operating temperatures, and adsorption/desorption cycle time on the specific cooling power, coefficient of performance, and the chiller efficiency are summarized.